CO2 GAS TRANSMISSIVITY OF NICKEL-BASED METAL- ORGANIC FRAMEWORKS/POLYSULFONE MIXED MATRIX MEMBRANES - Susianto, Nirwan
Conventional CO2 gas separation via cryogenic distillation or amine-based absorber is energy-intensive and environmental unfriendly.Therefore,better energy efficiency membrane-based gas separation is intensively developed nowadays. One strategy to improve membrane separation performance is to fabricate mixed matrix membranes by dispersing inorganic fillers inside polymer matrices so that superiority of separation by porous fillers and easability of polymer processing can be combined. In this study, we develop mixed-matrix membranes using nickel-based metal-organic frameworks (MOF) inside polysulfone (PSf) matrices. Nickel-based MOFs were synthezised by solvothermal method at 120°C for 24 h using H2O/DMF mixture as solvent, two different salt precursors, NiCl2 and Ni(CH3COO)2, and two different linker ligands, benzen-1,4-dicarboxylic acid (H2BDC) and 2- aminobenzen-1,4-dicarboxylic acid (H2BDC-NH2). Thus, we obtained four types of MOF with different structures, namely Ni(Cl)-BDC, Ni(OAc)-BDC, Ni(Cl)- NH2BDC, and Ni(OAc)-NH2BDC. Membrane was fabricated by solution casting method that MOF and PSf were homogeneously dispersed in chloroform. X-ray diffraction patterns from four Ni-MOF shows distinct MOF’s crystal structure from each combination of precursor salts and linker ligands. Different nickel precursor salts leads to formation of different structure. MOFs’ synthesis from H2BDC linker ligands and NiCl2 salts yielded Ni3(OH)2(H2O)2(BDC)2 diaqua phase, but if Ni(CH3COO)2 is used instead of NiCl2, it yielded Ni3(OH)2(H2O)4(BDC)2 tetraaqua phase. The main difference between these two phases is the number of coordinated H2O molecules on Ni2+. MOFs’ synthesis using H2BDC-NH2 linker ligand and Ni(CH3COO)2 salt was turned out to be a new structure that hasn’t been identified until now. FTIR spectra of Ni(Cl)-NH2BDC and Ni(OAc)-NH2BDC shows N?H stretching peaks from ?NH2 functional group at 3300?3400 cm?1, apart from COO asymmetric and symmetric stretching peaks respectively at 1560?1590 cm?1 dan 1380?1400 cm?1 region, which are also found on Ni(Cl)-BDC dan Ni(OAc)-BDC. BET surface area of Ni(Cl)-BDC, Ni(OAc)-BDC, Ni(Cl)-NH2BDC, and Ni(OAc)- NH2BDC were 12,097 m2/g; 40,225 m2/g; 16,037 m2/g; and 14,020 m2/g, respectively. FTIR-ATR spectra from membrane sample shows neither shifting peaks nor new peaks different from MOF and PSf indicating that interaction